Asymptotic approximation of solution to quasilinear elliptic boundary-value problem in a two-level thick junction of type 3:2:2 - Sadovyj, D.Yu. (Carpathian Mathematical Publications, 2012)
We consider quasilinear elliptic boundary-value problem in a two-level thick junction $Ω_ε$ of type 3:2:2, which is the union of a cylinder $Ω_0$ and a large number of $ε$-periodically situated thin discs with varying thickness. Different Robin boundary conditions with perturbed parameters are given on the surfaces of the thin discs. The leading terms of the asymptotic expansion are constructed and the corresponding estimate in Sobolev space is obtained.